Evaluating Sip Awareness On Investment Choices Among Bengaluru It Professionals - Thangarajan, Radha; Prabhakaran J, Prabhakaran J; Paramasivan, Senthilmurugan; Sunkapur, Santosh M; Panda, Sasmita; Poojari, Sangappa (Journal of Neonatal Surgery, 2025)
The mutual fund industry in India is growing rapidly and is one of the key sectors driving the nation's economic expansion. It holds immense potential for sustained growth in the future. Over the past decade, mutual funds, including instruments such as systematic investment plans (SIPs), equity funds, debt funds, and hybrid funds, have contributed significantly to the economy, benefiting both corporations and individuals. This study focuses on SIPs, which have become a popular investment choice for many, offering a balanced approach to generating returns while minimizing risks through regular investments. SIPs are attractive because they provide ease, affordability, and accessibility in saving and investing. They also offer advantages like professional management, diversification, liquidity, and transparency, all under strict government regulation. The research investigates various factors influencing SIP investment decisions, especially the awareness of SIPs among information technology (IT) employees. It also explores how demographic variables—such as age, income, and education—affect engagement in SIPs. The main aim is to assess how awareness of SIPs influences investment choices. Primary data from 112 IT employees in Bangalore was analyzed using SPSS software. The results show that while IT employees are aware of SIPs, their understanding of the specifics is limited. Awareness significantly impacts investment decisions, highlighting the need for better information dissemination about SIPs and their benefits